Teneurin Structure: Splice Variants of a Bacterial Toxin Homolog Specifies Synaptic Connections - Araç, Demet; Li, Jingxian (Frontiers in Neuroscience, 2019)
Teneurins are a conserved family of cell-surface adhesion molecules that mediate cellular communication, and play key roles in embryonic and neural development. Their mechanisms of action remained unclear due in part to their unknown structures. In recent years, the structures of teneurins have been reported at atomic resolutions and revealed a clear homology to bacterial Tc toxins with no similarity to other eukaryotic proteins. Another surprising observation was that alternatively spliced variants of teneurins interact with distinct ligands, and thus specify excitatory vs. inhibitory synapses. In this review, we discuss teneurin structures that together with structure-guided biochemical and functional analyses, provide insights for the mechanisms of trans-cellular communication at the synapse and other cell-cell contact sites.